It’s time to eliminate the mismatch between pediatric training and practice - Frank Oberklaid (BMC, 2021)
Abstract The quality of pediatric clinical practice is dependent on the training received during residency. It is assumed that the content of the training will adequately prepare pediatricians for the sorts of problems and issues they will be asked to manage in community settings. While over the past several decades there have been major changes in pediatric morbidity, there is evidence that training and service delivery models have not evolved; there is a significant mismatch between training and evidence-based clinical practice. A recent paper published in this journal (1) drew attention to the inadequacy of pediatricians’ training in child development. The reality of major gaps in the content and experiences of pediatric training in Israel are widely held, and there have been repeated calls for an increased focus on community child health and developmental and behavioural pediatrics. While it appears that finally there are some small initial steps to this end, it is strongly recommended that there be a long overdue, radical rethink of pediatric training programs.